15-11(3m-2)+4(8m-9)-10=

Simple and best practice solution for 15-11(3m-2)+4(8m-9)-10= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-11(3m-2)+4(8m-9)-10= equation:


Simplifying
15 + -11(3m + -2) + 4(8m + -9) + -10 = 0

Reorder the terms:
15 + -11(-2 + 3m) + 4(8m + -9) + -10 = 0
15 + (-2 * -11 + 3m * -11) + 4(8m + -9) + -10 = 0
15 + (22 + -33m) + 4(8m + -9) + -10 = 0

Reorder the terms:
15 + 22 + -33m + 4(-9 + 8m) + -10 = 0
15 + 22 + -33m + (-9 * 4 + 8m * 4) + -10 = 0
15 + 22 + -33m + (-36 + 32m) + -10 = 0

Reorder the terms:
15 + 22 + -36 + -10 + -33m + 32m = 0

Combine like terms: 15 + 22 = 37
37 + -36 + -10 + -33m + 32m = 0

Combine like terms: 37 + -36 = 1
1 + -10 + -33m + 32m = 0

Combine like terms: 1 + -10 = -9
-9 + -33m + 32m = 0

Combine like terms: -33m + 32m = -1m
-9 + -1m = 0

Solving
-9 + -1m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -1m = 0 + 9

Combine like terms: -9 + 9 = 0
0 + -1m = 0 + 9
-1m = 0 + 9

Combine like terms: 0 + 9 = 9
-1m = 9

Divide each side by '-1'.
m = -9

Simplifying
m = -9

See similar equations:

| 5x-2/3(3x-9) | | 7=91 | | -5x+6x-7=7x+5 | | x(2x-8)=(2x+8)(x-6) | | -6x-7y=10 | | .50x+.45(50)=27.5 | | 4n+2=6(0.333n-0.666n) | | 8x+1=100 | | -5(4n+4)+5n=-80 | | 70=a+(a-36) | | 4(20-0.5y)-2y=150 | | 9x+11=x+4 | | (3x-2)^(5/3)=6 | | 4x-2(-0.5y)=120 | | -5(4n+4)+5n=80 | | 17x+3x+15x+21+4=87 | | -5(4n+4)+5n= | | x^2+6x+9=26 | | 12t-8m=-52 | | 4.2+4=3x+9.4 | | (3x-9)/(x-4) | | -250x-3= | | b-7/4= | | B-7/4 | | 9(x+8)+12=8(x+8)10 | | x6/x3= | | 3.5=-7y+21 | | 9(x+8)*12=8(x+8)+10 | | (10+10)x+x=2 | | 21+3x+1=57 | | 14(8+12)= | | f(x)=-x^2-4x-8 |

Equations solver categories